Effect of Iced Storage Duration and Treatments on the Frozen Storage Characteristics of Cuttlefish Fillets - P.M., Sherief; Joseph, Sophia Margaret (Fishery Technology, 2025)
Effect of iced storage duration and treatments with 2% (w/v) salt + 0.2% (w/v) citric acid solution and with 0.01% (w/v) butylated hydroxy anisole (BHA) solution, each for 10 min was studied in frozen stored cuttlefish fillets. The salt + citric acid treatment was found to be superior in retaining the texture, physical appearance and overall quality of the frozen fillets. Yellow discolouration was observed on the control samples (4-d iced) after eight weeks of frozen storage. A Maillard type reaction is postulated as the possible cause of yellow discolouration in frozen stored cuttlefish fillets.